Asymmetric succession in soil microbial communities enhances the competitive advantage of invasive alien plants - Mengxin Zhao; Yunfeng Yang; Han Zhang; Qiao Li; Xiaoxun Zhao; Xue Guo; Wanxue Liu; Fanghao Wan (Microbiome)
Abstract Background Biological invasions pose an escalating threat to native ecosystems. The accumulation of invasive alien plants worldwide is not saturated yet, underscoring the persistent and growing impact of invasions. Soil microorganisms play a key role in the process of alien plant invasion. However, the temporal dynamics of microbial communities has rarely been determined during the invasion owing to the dearth of long-term, in situ experimental systems. Results Here, we examined the temporal succession of soil microbial communities 8 years after experiment setup in a common garden. Bacterial communities displayed divergent temporal succession, with invasive plants exhibiting higher turnover rates. Invasive alien plants reduced stochasticity in bacterial communities, likely acting as an environmental filter on community assembly. Plant growth-promoting microbes underwent higher succession rates in invasive alien plants compared to native plants, suggesting that invasive alien plants may possess a distinct advantage in fostering a favorable microbiota for their own growth and establishment. In sharp contrast, native plants selectively increased succession rates of specific plant pathogens. Furthermore, the microbial co-occurrence network was more complex in invasive plants, suggesting that invasive plants foster intricate relationships among microbial communities. Conclusions Therefore, the asymmetric succession in soil microbial communities enables invasive plants recruit beneficial microbiota from the surrounding soil. These results deepen our understanding of the mechanism underlying plant invasion and provide novel insights into predicting the ecological consequences resulting from widespread plant invasion. This knowledge can be incorporated into management strategies to address the evolving challenges posed by invasive plants. Video Abstract